(untitled) (Research, Society and Development, 2021)
Students’ difficulties in learning concepts are a currently challenge faced by Physics teachers during the teaching-learning process. The use of technologies as teaching tools is one of the ways adopted by teachers to minimize this kind of problem. However, despite the positive results that have been obtained by the use of these technologies in the Physics teaching, there are still few applications developed for Android® smartphones with the purpose of use in the classroom to address Physics concepts. Thus, the present study aimed the development of an Android® app using the FlingAnimation class for initial approaches of kinematics concepts. For the app development, the Java language was used through the Android Studio development environment. The class FlingAnimation was used for the animation of the object proposed in the app, which is a class developed by Google to support animations in apps. The app shows the straight trajectory of a ball in a simulation as a point object. Finally, a didactic proposal is presented to explore the app with students in order to elucidate its functionalities and to approach, initially through a visual perception, how the variation of the acceleration module interferes on the movement of a body.